Dependence between rontgenologic peculiarities of skull bones and hormone abnormalities at women of fertile ages - E. V. Korneeva; V. I. Korchin (Бюллетень сибирской медицины)
In the present work the information about roentgens of skull bones at women of fertile period with polycystosis of ovaries and hypoactivity of thyroid gland is presented. It is revealed that more frequently met rontgenologic factors at patients with this pathology are small turkish saddle, narrowing of entrance in turkish saddle, endocraniosos and craniostenosis.